Preparation and characterization of geraniol nanoemulsions and its antibacterial activity - Feng, Xiaolin; Feng, Kexin; Zheng, Qinhua; Tan, Weijian; Zhong, Wenting; Liao, Caiyu; Liu, Yuntong; Li, Shangjian; Hu, Wenzhong (Frontiers in Microbiology, 2022)
Geraniol nanoemulsions (G-NE) based on Tween 80 and medium chain triglyceride (MCT) as surfactant and co-surfactant, respectively, has been prepared by the spontaneous emulsification method. Its physical and chemical properties such as mean particle size, zeta potential, PDI, pH, viscosity, contact angle, appearance morphology, and stability (storage stability, thermal stability, centrifugal properties, acid-base stability, and freeze-thaw properties) of the droplet were analyzed. The results showed that the mean particle size of G-NE was 90.33 ± 5.23 nm, the PDI was 0.058 ± 0.0007, the zeta potential was -17.95 ± 5.85 mV and the encapsulation efficiency was >90%. The produced G-NE has been demonstrated to be fairly stable in long-term storage at 4 °C, pH=5 and high-speed centrifuges. Moreover, G-NE had a significant inhibition effect on Staphylococcus aureus, Escherichia coli, Salmonella typhimurium and Listeria monocytogenes (p<0.05). The bacterial inhibition rates of G-NE at a concentration of 1 MIC were 48%, 99%, 71.73% and 99% after 12 hours of action against these four foodborne pathogenic bacteria, respectively. Therefore, the results obtained indicated that nanoemulsification enhanced the stability and antibacterial activity of geraniol to some extent, which will promote the utilization of geraniol in food preservation.